Attitudes and behaviours of Canadian National Team coaches regarding the use of technology in their coaching practice - Jaswal, M.; Stergiou, P.; Katz, L. (Journal of Human Sport & Exercise, 2019)
Previous literature has proposed that successful adoption measures involve positive attitudes regarding using technology, high levels of technological self-efficacy beliefs, low levels of perceived complexity, and high levels of perceived relative advantage. The purpose of this study is to investigate these antecedents of technology adoption among national team Canadian coaches. Twenty-five current and retired Summer and Winter Canadian national team coaches participated in this investigation. They completed four questionnaires: a general information form, the Affinity for Technology Interaction Scale (ATI), the Computer Self-Efficacy Measure (CSEM), and the Perceived Relative Advantage and Perceived Complexity Scales (PRA/PCo). Canadian national team coaches who responded were found to have a moderate affinity for technology when engaging with technology in their coaching practice. They also reported to have very high self-efficacy when it comes to using technology. They were shown to have a moderately high conviction in their ability to use technology. Coaches also viewed technology as giving them a high relative advantage over not using technology. Finally, they generally viewed technology as not very complex to operate. Most Canadian national team coaches who responded showed favourable views regarding using technology, had belief in their ability, and seemed capable of overcoming challenges in using technology. Future investigations should also identify elite coaches who do not use innovations and focus on sport specific challenges in adopting or implementing technology, as well as identifying barriers coaches face when acquiring or using new technology.